FACTORS AFFECTING LEVEL OF PREPAREDNESS FOR MENOPAUSE AMONG PRE-MENOPAUSAL WOMEN IN LEO COMMUNITY, IDO LOCAL GOVERNMENT AREA, OYO STATE, NIGERIA (2014)
Menopause is a phase in women’s reproductive life often characterized with many health challenges. Previous studies have revealed that there are gaps in knowledge, wrong perceptions and level of preparedness relating to menopause among pre-menopausal women. This study explored level of preparedness for menopause among pre-menopausal women in Leyaju, Elere and Oloko (LEO) community, Ido Local Government Area of Oyo State. Study sample was calculated using Kish and Leslie formular and a three-stage random sampling technique was used in selecting 426 women aged 30-44 years from LEO community. Six Focus Group Discussions (FGDs) were conducted to determine the discussants level of preparedness for menopause, their knowledge and perception about menopause. A validated interviewer administered questionnaire containing 33-point knowledge and 5-point level of preparedness scales were used to collect data on socio-demographic characteristics, knowledge of menopause and level of preparedness. Scores of ≤ 16 and ≥ 17 points were regarded as low and high knowledge respectively while scores of ≤ 1, 2 and ≥ 3 were considered as not prepared, slightly prepared and very prepared respectively. Quantitative data were analysed using descriptive, Chi-square and logistic regression while qualitative data were subjected to content analysis. The mean age of the respondents was 36.6  4.5 years and 86.9% were married. About eleven percent of the respondents had no formal education and 40.6% had secondary education. Majority (89.0%) of the respondents were Yoruba and 76.0% had ever heard about menopause. Sources of information on menopause included, relatives (36.0%), health care providers (18.1%), radio (13.4%), friends (12.0%) and internet (2.1%). Respondents’ mean knowledge score on menopause was 11.6  2.5. The mean knowledge scores by level of preparedness were: not prepared (5.7 ± 2.1), slightly prepared (10.6 ± 2.9) and very prepared (18.5 ± 2.5) with a significant difference (p<0.05). Only 45.8% of respondents were prepared for menopause and of this, 49.5% viewed themselves as very prepared. Less than half (28.4%) of the respondents aged 30-34 years and 56.9% of respondents aged 40-44 years were prepared for menopause (p<0.05). Respondents’ level of education was not significantly associated with the knowledge of menopause. Women who had good knowledge about menopause were more likely (O.R=5.0, C.I=2.3-10.7) to be prepared for menopause than those who had poor knowledge. The FGD participants expressed concerns about the health challenges related to menopause. A few of the participants opined that menopause gets in the way of conception. Levels of preparedness and knowledge of menopause were poor. Public enlightenment and community-based education on menopause should be directed towards improving knowledge and level of preparedness for menopause among young women.